2022
DOI: 10.1371/journal.ppat.1010962
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of an N-AChR from Brugia malayi, an evolved change in acetylcholine receptor accessory protein requirements in filarial parasites

Abstract: Neurotransmission is an important target for anthelmintic drugs, where receptor characteristics and response can be examined through reconstitution ex vivo in Xenopus laevis oocytes. The homomeric ACR-16 nicotine sensitive acetylcholine receptors (N-AChRs) of several helminth species have been characterized in this way. Our efforts to reconstitute the N-AChR from the clade III filarial parasite, Brugia malayi using similar conditions, initially produced no detectable response. A robust response to acetylcholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 87 publications
(286 reference statements)
0
30
2
Order By: Relevance
“…This is in contrast to the closely related pig parasite A. suum ACR-16 which requires its co-injection for function 56,61 . A. suum and D. medinensis ACR-16 receptors have similar pharmacology and identical maximal response, yet they have dramatically different requirements for the accessory protein 61 . Since the co-injected RIC-3 was constant, the cause must be encoded in their sequences, which differ by only 16 %.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…This is in contrast to the closely related pig parasite A. suum ACR-16 which requires its co-injection for function 56,61 . A. suum and D. medinensis ACR-16 receptors have similar pharmacology and identical maximal response, yet they have dramatically different requirements for the accessory protein 61 . Since the co-injected RIC-3 was constant, the cause must be encoded in their sequences, which differ by only 16 %.…”
Section: Discussionmentioning
confidence: 78%
“…We previously reported that D. medinensis ACR-16 no longer required RIC-3 co-injection for function in the oocyte expression system, whereas the closely related A. suum ACR-16 did 61 . Their high sequence identity (84%) provided an opportunity to identify the sequence responsible (Figure S1A).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations